Assessing the feasibility of a bowel management program for patients with neurogenic bowel function after spinal cord injury - Feng, Jiayi; Mu, Xingyi; Xu, Lei; Xia, Tongxia (Frontiers in Medicine, 2025)
The aim of this study was to assess the feasibility of a bowel management program for patients with neurogenic bowel function after spinal cord injury. The program is based on evidence-based nursing, expert meeting and pre-experiment construction, the construction process is standardized and scientific, and the content is comprehensive, mainly includes 4 dimensions of bowel assessment, bowel intervention, assessment indices and discharge follow-up, which were carried out at the time of admission (T1), discharge (T2) and 1 month after discharge (T3) of patients in the experimental group, while the control group used routine orthopedic bowel management, and bowel function indices, quality of life and laboratory tests were used as outcome indices, and differences in the observed indices of patients in the two groups were compared to validate the effect of the program. Compared with the control group, the incidence of bloating, constipation and fecal incontinence was significantly reduced in the experimental group, while the frequency of defecation scores, fecal character scores, Neurogenic Bowel Dysfunction scores, laboratory test results and quality of life were also effectively improved. The results also highlight the need for a large, multi-center, long-term follow-up study to validate the efficacy of this protocol to improve the feasibility of bowel management protocols for patients with neurogenic bowel function after spinal cord injury. This study provides a reference base for further exploration of bowel management in patients with neurogenic bowel function after spinal cord injury and is worthy of promotion and application in clinical practice.